The Characteristics of Physicochemical and Functional Properties of North Sumatera Wheat Flour - Siti Nur Janna Sihotang; Zulkifli Lubis; Ridwansyah Ridwansyah (Jurnal Rekayasa Pangan dan Pertanian, 2015)
Indonesian people consume much wheat flour, whereas wheat was not grown in Indonesia and must be imported. Therefore a research of the quality of wheat that can be grown in Indonesia was made in order to reduce import. This research was aimed to study the seed, physicochemical and functional characterization of north Sumatera wheat flour. This research had been performed using non factorial completely randomized design. Parameters analyzed were seed hardness, bulk density, moisture content, ash content, fat content, crude fiber content, protein content, water absorption, oil absorption capacity, swelling power, and baking expansion. Keyword: Flour, furrow, variety, wheat.